ISM NAKIRAH (NOMINA INDEFINIT) DANISM MA’RIFAH (NOMINA DEFINIT) DALAM TEKS BACAAN AL-‘ARABIYYAH BAINA YADAIK JILID 4 JUZ 2(ANALISIS SINTAKSIS): ISIM NAKIRAH (INDEFINITE NOMINA) AND ISIM MA'RIFAH (DEFINITE NOMINA) IN THE AL-'ARABIYYAH BAINA YADAIK TEXTBOOK VOLUME 4 PART 2 (SYNTAXIC ANALYSIS) - Azka, Ianah Millati; Ahmad Hasyim, Mohamad Yusuf (Universitas Negeri Semarang, 2025)
Studying nahwu means studying the rules governing the usage of Arabic sentences, encompassing their structure, position, and grammatical markers. In nahwu studies, understanding ism nakirah (indefinite noun) and ism ma’rifah (definite noun) is crucial due to the significant impact of the article